2020
DOI: 10.1097/bpb.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

An insight of how multiple skeletal maturity indices can be used for growth assessment: relationship between the simplified olecranon, simplified digital, and distal radius and ulna classifications

Abstract: This cross-sectional study aims to investigate the relationship between the simplified olecranon, simplified digital, and distal radius and ulna (DRU) classifications, and whether they can aid in more comprehensive maturity assessment together. Left hand and wrist and lateral elbow radiographs from pediatric patients were assessed using the three skeletal maturity indices. The association between maturity indices was investigated using Goodman and Kruskal’s gamma, and by mapping of individual grades based on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, one study by Canavese and colleagues compared the Dimeglio method (the predecessor to the OAOSS) and the Sanders Hand system during the pubertal growth spurt and found they were equally reliable. This study, along with several others, also suggests combining different skeletal maturity systems may improve growth prediction accuracy, particularly during different periods of growth 22,25,26 . In reality, some systems likely perform better than others due to inherent differences in calibration technique, addition of new parameters, or underlying variability in radiographic positioning 27 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, one study by Canavese and colleagues compared the Dimeglio method (the predecessor to the OAOSS) and the Sanders Hand system during the pubertal growth spurt and found they were equally reliable. This study, along with several others, also suggests combining different skeletal maturity systems may improve growth prediction accuracy, particularly during different periods of growth 22,25,26 . In reality, some systems likely perform better than others due to inherent differences in calibration technique, addition of new parameters, or underlying variability in radiographic positioning 27 .…”
Section: Discussionmentioning
confidence: 59%
“…While these systems have been individually validated against the GP standard, several studies have observed intersystem discrepancies in BA estimates, especially among upper extremity systems. [19][20][21][22] A recent study comparing the GP system to the Sauvegrain method, which uses anteroposterior and lateral elbow radiographs, in children treated for limb-length discrepancy found 66% of patients had BA assessments that differed by at least 6 months. 21 Inconsistencies of this degree could have major impacts on surgical planning.…”
mentioning
confidence: 99%
“…it is also prudent to note that the cobb angle at brace weaning is another risk factor of progression after maturity. [49][50][51][52] Patients with cobb angle reaching 40° is a well-established cutoff for adulthood progression. 4,53 similarly, those with this benchmark at the time of brace-weaning also have the potential for post-maturity progression.…”
Section: Discussionmentioning
confidence: 99%
“…The use of both the simplified olecranon method and DRU classification provides adequate coverage of the prepubertal and growth acceleration phases, and the DRU and simplified digital methods provide assessment beyond peak height velocity for the decelerating growth phase until skeletal maturity. Therefore, the crucial peak height velocity can be assessed with the combination of the 3 systems complementing each other 7 .…”
Section: Lower-limb Assessmentmentioning
confidence: 99%